DAMPAK POSITIF EVALUASI PEMBELAJARAN TERHADAP PRESTASI BELAJAR SISWA KELAS 4 SD NEGERI BLOTONGAN 03 JAWA TENGAH TAHUN PELAJARAN 2018/2019 - Nur Endah Hikmah Fauziyah (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2019)
The purpose of this study was to determine the positive impact of learning evaluation on the learning achievement of 4th grade students of SD Negeri Blotongan 03. The type of research used in this study is quantitative research. In this study using descriptive methods. The sample of this study is 4th grade student of SD Negeri Blotongan 03 even semester of the school year 2018/2019 which is thirty. The instruments in this study included observation, questionnaires, field notes, and interviews. Then analyzed using quantitative data, namely bi summing the result of the questionnaire in each number. The results of the study obtained that through various kinds of evaluations of learning carried out by teacher for 4th grade students of SD Negeri Blotongan 03 show result that have a positive impact in the scope of 4 eduction domain, namely cognitive, spiritual, affective, and psychomotor.